Job satisfaction and service quality gap in public universities in the east coast of Malaysia - Wan Norhayati Mohamed (Fakulti Pengurusan Ekonomi, 2011)
The increasing number of public and private university indicates that the competition in the higher education industry in Malaysia is becoming volatile. In order to compete effectively in the marketplace, an educational institution needs to differentiate itself from their competitors. Similar to other firms in service sector, perhaps, the only way the higher education institutions can differentiate themselves from their competitors is through delivering high quality service.